Hybrid coagulation ultrafiltration for tenun dye waste water treatment - Hashima Abu, Hasan (2014)
Hybrid Coagulation UF process has been studied to improve membrane performance and water quality for surface water treatment. Using coagulation before UF increases permeate quality; the extent of dissolved organic matter removal is controlled by the coagulation step. Efficient coagulation conditions for coagulation / settling process can be applied for the hybrid coagulation UF process. Floc cake resistance is lower than resistance due to the unsettled floc and the uncoagulated organics. For this research the hybrid process was applied in attempt to treating the effluent wastewater that discharged from the textile industries. The Hybrid Coagulation UF model was setup using the apparatus that already prepared at environmental laboratory. The waste water sample with addition of predetermined dosage of Aluminum Sulphate (Al 2(SO4)3 ) which has been left for 24 hours and 48 hours was filtered using the membrane filter with pore size 0.1 - 0.4 j.i with the bar pressure used is between 3 - 4 bars. The filtered sample was taken to measure the parameters which are COD, BOD, TSS and Colour. Then the results were compared between the raw sample and after treatment sample. The application of the hybrid system, combining coagulation and ultrafiltration, offers better effects of the removal of organic pollution.